FINANCIAL MANAGEMENT PRACTICES BASED ON TRIDENT VALUES AT DARUL ULUM UNIVERSITY JOMBANG - Hevi Susanti; Lilis Ardini; Nur Handayani (SOSIOEDUKASI, 2026)
This study aims to examine more deeply the practice of financial management based on trident values at Universitas Darul Ulum Jombang. This research is a qualitative research with an emphasis on exploring information in depth on key informants. There are 3 key informants in this study. Data was obtained by in-depth documentation and interviews, then processed in three stages, namely data reduction, data presentation to conclusion drawing using the Miles and Hubermen model. The results of the study show that in the diversity there are also values that must be carried out by the academic community of Darul Ulum University which is based on the values of the trident, namely obedience to teachers, diligence, honesty, patience, and sincerity. with the model of financial management practices from the planning stage, the existence of applicable regulations, openness, the preparation of RAB and RABRT, setting short and long-term goals, the allocation of funds can be balanced by referring to the proirity of the campus, at the recording stage there are procedures in bookkeeping, consistent, accurate recording, real time, transparency, the use of applications is very supportive in compiling financial statements. At the reporting stage, being able to present monthly and annual reports in accordance with the PSAK ETAP standards will be easier and more timely, accurate, and the data produced is guaranteed to be safe, relevant data to be reported, patient and very thorough in making the report. At the control stage with honest and fair control of all financial activities in accordance with the plan and objectives of continuing to carry out existing procedures, with academic guidelines, Statutes, Strategic Plans, Renop, SOPs, and applicable policies, Objectives, openness between employees and leaders and policies to implement good financial management that have been communicated by stakeholders. In practice, financial management is still based on Internal Quality Audit or LPJM, and still maintains good and effective communication.